Hubungan Antara Dukungan Sosial Keluarga dengan Kualitas Hidup Pada Lansia Di Nagari Paninjauan Kec. X Koto Diatas Kab. Solok - Ria Okfrima; Erika Prima Yola; Harry Theozard Fikri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The purpose of this research is to know the relationship between family social support with the quality of elderly life in Nagari Paninjauan Kecamatan X Koto Diatas, Kabupaten Solok. The dependent variables in this study are quality of life and independent variables are family social support. The measuring instrument used in this study is the family social support scale that researchers compiled based on the theory put forward by House (in Suparni, 2016) and the quality of life scale that researchers compiled based on the theory expressed by WHO Called WHOQOL (World Health Organization Quality of Life). The population in this study was the elderly in Nagari Ogan which amounted to 291 elderly. As for the determination of the subject of this study using Simple Random Sampling technique in which the researchers mix the subjects within the population so that all subjects are considered equal, and the samples in this study were 25% of the population of 73 elderly in Nagari Paninjauan, Kabupaten Solok. The data analysis method used for the hypothesis testing in this study is to use the (Pearson) correlation of Produc moment, which indicates that rxy = 0.415 with a value of P = 0.000 (< 0.01), which means there is a significant relationship between family social support with quality of life in the elderly in Nagari Paninjauan, Kabupaten Solok medium category. Means research hypothesis is acceptable. The effective contribution of family social support variables to the quality of life is a much as 17%.